Solve for x
x = -\frac{27}{2} = -13\frac{1}{2} = -13.5
x=5
Graph
Quiz
Quadratic Equation
5 problems similar to:
\frac { 27 + x } { 12 x + 36 } = \frac { 3 } { 2 x - 1 }
Share
Copied to clipboard
\left(2x-1\right)\left(27+x\right)=\left(12x+36\right)\times 3
Variable x cannot be equal to any of the values -3,\frac{1}{2} since division by zero is not defined. Multiply both sides of the equation by 12\left(2x-1\right)\left(x+3\right), the least common multiple of 12x+36,2x-1.
53x+2x^{2}-27=\left(12x+36\right)\times 3
Use the distributive property to multiply 2x-1 by 27+x and combine like terms.
53x+2x^{2}-27=36x+108
Use the distributive property to multiply 12x+36 by 3.
53x+2x^{2}-27-36x=108
Subtract 36x from both sides.
17x+2x^{2}-27=108
Combine 53x and -36x to get 17x.
17x+2x^{2}-27-108=0
Subtract 108 from both sides.
17x+2x^{2}-135=0
Subtract 108 from -27 to get -135.
2x^{2}+17x-135=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-17±\sqrt{17^{2}-4\times 2\left(-135\right)}}{2\times 2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 2 for a, 17 for b, and -135 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-17±\sqrt{289-4\times 2\left(-135\right)}}{2\times 2}
Square 17.
x=\frac{-17±\sqrt{289-8\left(-135\right)}}{2\times 2}
Multiply -4 times 2.
x=\frac{-17±\sqrt{289+1080}}{2\times 2}
Multiply -8 times -135.
x=\frac{-17±\sqrt{1369}}{2\times 2}
Add 289 to 1080.
x=\frac{-17±37}{2\times 2}
Take the square root of 1369.
x=\frac{-17±37}{4}
Multiply 2 times 2.
x=\frac{20}{4}
Now solve the equation x=\frac{-17±37}{4} when ± is plus. Add -17 to 37.
x=5
Divide 20 by 4.
x=-\frac{54}{4}
Now solve the equation x=\frac{-17±37}{4} when ± is minus. Subtract 37 from -17.
x=-\frac{27}{2}
Reduce the fraction \frac{-54}{4} to lowest terms by extracting and canceling out 2.
x=5 x=-\frac{27}{2}
The equation is now solved.
\left(2x-1\right)\left(27+x\right)=\left(12x+36\right)\times 3
Variable x cannot be equal to any of the values -3,\frac{1}{2} since division by zero is not defined. Multiply both sides of the equation by 12\left(2x-1\right)\left(x+3\right), the least common multiple of 12x+36,2x-1.
53x+2x^{2}-27=\left(12x+36\right)\times 3
Use the distributive property to multiply 2x-1 by 27+x and combine like terms.
53x+2x^{2}-27=36x+108
Use the distributive property to multiply 12x+36 by 3.
53x+2x^{2}-27-36x=108
Subtract 36x from both sides.
17x+2x^{2}-27=108
Combine 53x and -36x to get 17x.
17x+2x^{2}=108+27
Add 27 to both sides.
17x+2x^{2}=135
Add 108 and 27 to get 135.
2x^{2}+17x=135
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{2x^{2}+17x}{2}=\frac{135}{2}
Divide both sides by 2.
x^{2}+\frac{17}{2}x=\frac{135}{2}
Dividing by 2 undoes the multiplication by 2.
x^{2}+\frac{17}{2}x+\left(\frac{17}{4}\right)^{2}=\frac{135}{2}+\left(\frac{17}{4}\right)^{2}
Divide \frac{17}{2}, the coefficient of the x term, by 2 to get \frac{17}{4}. Then add the square of \frac{17}{4} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{17}{2}x+\frac{289}{16}=\frac{135}{2}+\frac{289}{16}
Square \frac{17}{4} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{17}{2}x+\frac{289}{16}=\frac{1369}{16}
Add \frac{135}{2} to \frac{289}{16} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{17}{4}\right)^{2}=\frac{1369}{16}
Factor x^{2}+\frac{17}{2}x+\frac{289}{16}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{17}{4}\right)^{2}}=\sqrt{\frac{1369}{16}}
Take the square root of both sides of the equation.
x+\frac{17}{4}=\frac{37}{4} x+\frac{17}{4}=-\frac{37}{4}
Simplify.
x=5 x=-\frac{27}{2}
Subtract \frac{17}{4} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}